Programming in C for foundation - Bakar, Noor Hasrina; Hassan, Noor Azimah; Idris, Mohd Norhaedir; Al-Shawabkeh, Mahmoud (IIUM Press, 2014)
This book on C programming language is a comprehensive tutorial and reference to C based on the ANSI C standard for beginners. The C language is demonstrated with numerous examples and extensive exercises that guide readers through each concept. Step-by-step of program code reveal the underlying logic of the programs and include in-depth implementation details. Features in this book include comprehensive programming examples and exercises; and an expanded appendix of Numbering System, ASCII Code, and DevC++ tutorial. In addition, there is more emphasis on variable Data Types, which provides the reader with a foundation for working with variables and facilitates programming in the problem domain. Beginners’ programmers alike will benefit from the numerous examples and extensive exercises developed to guide readers through each concept. Program codes illuminate the correct usage and syntax of C language and reveal the underlying logic of application. The clarity of exposition and format of the book make it an excellent reference to first step programmers. It is intended for use in either a foundation level or first year programming course.